Kodály today : a cognitive approach to elementary music education - Houlahan, Mícheál; Tacka, Philip (Kodály today handbook series., 2015)
In this new edition of their groundbreaking Kodaly Today, Micheal Houlahan and Philip Tacka offer an expertly-researched, thorough, and -- most importantly -- practical approach to transforming curriculum goals into tangible, achievable musical objectives and effective lesson plans. Their model -- grounded in the latest research in music perception and cognition -- outlines the concrete practices behind constructing effective teaching portfolios, selecting engaging music repertoire for the classroom, and teaching musicianship skills successfully to elementary students of all degrees of profici.